A trade-off between tax reporting and financial reporting aggressiveness based on financial variables - Acropolis Gemilang Mada Ngara Ledewara; Ari Budi Kristanto; Maria Rio Rita (Jurnal Keuangan dan Perbankan, 2020)
Firms likely exhibit greater financial reporting aggressiveness to increase their earnings and eventually attract investors. However, firms also tend to reduce their taxable income to maximize their cash flow. Consequently, firms arguably manage their corporate income tax aggressively. This research aims to investigate whether firms with low debt levels are more aggressive in their tax reporting than in financial reporting, firms with financial deficits are more aggressive in their financial reporting than in tax reporting, and firms with better access to external/internal capital market are more aggressive in their tax reporting rather than in financial reporting. We use three financial variables, namely debt ratios, financial deficits, and access to internal or external capital markets as proxies for firms’ financial condition. This study finds that all financial variables except financial deficits, motivate firms to engage in aggressive reporting decisions. Specifically, firms with higher debt ratios and easier access to external or internal capital markets will likely exhibit more aggressive tax reporting than financial reporting. JEL Classification: H26, G32, M41DOI: https://doi.org/10.26905/jkdp.v24i3.4018